Routledge Handbook of African Peacebuilding - Charbonneau, Bruno; Ricard, Maxime (Routledge, 2022)
The book begins by outlining the evolution and the various ideologies, conceptualizations, institutions, and practices of African peacebuilding. It identifies critical differences in how African peacebuilders have conceptualized and operationalized peacebuilding. The book then considers how different actors sustain, construct, and use African infrastructure to identify and analyse converging, differing, or competing mandates, approaches, and interests. Finally, it analyses specific thematic issues such as gender, justice, development, democracy, and the politics of knowledge before ending with in-depth analyses of case studies drawn from across the continent. Bringing together an international line-up of expert contributors, this book will be an essential read for students and scholars of African politics, post-conflict reconstruction, security, and peace and conflict studies.